RELATIONSHIP BETWEEN PARENTS INVOLVEMENT AND STUDENT’S SUCCESS AT SECONDARY SCHOOL LEVEL - RIAZ, ANUM; AWAIS, MUHAMMAD TAIMOOR (International Journal of Psychosocial Rehabilitation, 2020)
The gap between developing and developed countries is a gap of education. This current research thesis aims to elaborate the effect of parent involvement on student’s success in educational institutions. Education is a fundamental right of all the children. In order to implement the parents are also involve to enhance the qualities of the child and become them successful. The study based on analyze literature and providing guideline to researchers on how to find out the most important parent involvement dimensions for educational process of the child. In this study, the dependent variable is student success that measured by the independent variable parent involvement. The population was the parents of the secondary school students from Punjab, Pakistan. For the delimitation of the population 287parents of the secondary school students selected as sample of this study. Simple random sampling technique adopted for data collection by survey method. Data was collected through questionnaire comprise on 5 point Likert scale (1. Strongly disagree to 5. Disagree) format. The findings of the study revealed that there was significance between parenting and the success of students at secondary school level.